UPAYA MENINGKATKAN HASIL BELAJAR SENI BUDAYA MELALUI GAME TEBAK KATA PADA SISWA KELAS X BDPM 1 SMKN 2 DENPASAR SEMESTER 2 TAHUN 2022/2023 - Nazzala Sophie Yustina (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The word guessing game media is a game that is able to cultivate students' memories and cohesiveness among students in groups. The purpose of this study was to determine the development of charades media, the feasibility of charades media, and students' responses to charades media. This research uses cooperative learning method. This research was conducted at SMK Negeri 2 Denpasar in class X BDPM 1 which was tested on students. The research used qualitative and quantitative data collection methods and the results of the data obtained used Likert and Guttman scale scores. From the results of the study, it shows that the percentage of material experts obtained is 87% and media experts is 88%. From the questionnaire that was tested on 20 students, it was 96.5%. It can be concluded that the word guessing game media is appropriate to be used as a medium of learning in art and culture material.